DIGITALISASI KOLEKSI REALIA BERBASIS KONTEN GRAFIS DI PERPUSTAKAAN INSTITUT PERTANIAN STIPER YOGYAKARTA - Cindy Fadilah; Anis Masruri (JURNAL ILMU PERPUSTAKAAN (JIPER), 2024)
The aim of this research is to increase accessibility and user involvement through the use of digital technology in the context of the realia collection at the INSTIPER Yogyakarta library. By using graphic content, the library aims to present information in a more visual and interactive way, thereby enriching the user's experience in understanding and accessing the realia collection. The research method used is descriptive research with a qualitative approach. Data collection techniques used include observation and interviews. The data sources used include primary data directly from library users and staff as well as secondary data from documents and related literature. The data processing and analysis process includes data reduction, data presentation, and results verification. The results of this research show that the digitization of the realia collection based on graphic content in the INSTIPER Yogyakarta library includes three main stages. The first stage includes collecting and searching the realia collection available in the INSTIPER Yogyakarta library. The second stage includes the development of graphic content to present information about the realia collection visually and interactively. This can include creating infographics, 3D visualizations or animations that enrich the user experience. The final stage is the digitization of the realia collection itself, so that users can access it online via the library's digital platform.